2016
DOI: 10.20960/nh.261
|View full text |Cite
|
Sign up to set email alerts
|

Índice general de fuerza y adiposidad como medida de la condición física relacionada con la salud en niños y adolescentes de Bogotá, Colombia: Estudio FUPRECOL

Abstract: general de fuerza y adiposidad como medida de la condición física relacionada con la salud en niños y adolescentes de Bogotá, Colombia: Estudio FUPRECOL. Nutr Hosp 2016;33:556-564Índice general de fuerza y adiposidad como medida de la condición física relacionada con la salud en niños y adolescentes de Bogotá, Colombia: Estudio FUPRECOL AbstractObjective: The purposes were: a) to generate normative values of general strength index (GSI) scores of 9-to 17.9-year-olds; and b) to describe the associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
3
1
0
3
Order By: Relevance
“…This study also reveals, for the first time in Colombia, the normalized percentiles of muscular and cardiorespiratory performance by age and sex; values that can be used as a reference in the assessment of physical fitness concerning the nutritional status and body composition in the school population. In summary, and as established by different authors (Pacheco et al, 2016;Secchi et al, 2016), in the studied population, higher values of muscular and cardiorespiratory fitness were observed in the male school children evaluated, highlighting the significant increase as age increases, a difference explained mainly by the different factors of biological maturation.…”
Section: Discussionsupporting
confidence: 77%
“…This study also reveals, for the first time in Colombia, the normalized percentiles of muscular and cardiorespiratory performance by age and sex; values that can be used as a reference in the assessment of physical fitness concerning the nutritional status and body composition in the school population. In summary, and as established by different authors (Pacheco et al, 2016;Secchi et al, 2016), in the studied population, higher values of muscular and cardiorespiratory fitness were observed in the male school children evaluated, highlighting the significant increase as age increases, a difference explained mainly by the different factors of biological maturation.…”
Section: Discussionsupporting
confidence: 77%
“…El promedio de las dos variables transformadas se utilizó para establecer una única variable denominada índice de fuerza muscular (IFM), con valores comprendidos entre el cero y el uno (García-Artero et al, 2007;Pacheco-Herrera, Ramírez-Vélez, & Correa-Bautista, 2016;Rodríguez-García et al, 2015).…”
Section: Variables E Instrumentosunclassified
“…To date, there are no established reference cut-off points for MF, assessed using either handgrip strength or SLJ. Previous studies have shown that participants with low MF (lowest quartile) have the poorest cardio-metabolic profile [ 43 , 44 ]; therefore, suggesting that participants falling below the threshold for this quartile could be considered “unhealthy”. Taking this into account, we have used the 20 th percentile as a threshold for unhealthy MF, as reported in adolescents from Europe [ 40 ].…”
Section: Methodsmentioning
confidence: 99%